Zooremediation: Utilizing Animals for Environmental Purification and Pollution Mitigation - Aini, Fadita Nurul; Nisa, Upi Chairun; Handayani, Windri; Maryenti, Tety; Yasman, Yasman (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: The global human population continues to grow rapidly, leading to increasing urban waste and environmental contamination. One emerging and promising approach to mitigating this pollution is zooremediation, which utilizes animals as biological agents for environmental cleanup. This review aims to critically assess the effectiveness of various animal species in removing specific classes of pollutants, with particular attention to their mechanisms of action—zooextraction, zootransformation, and zooaccumulation—and the environmental conditions under which they operate. Effectiveness is evaluated based on pollutant removal efficiency, adaptability to contaminated environments, and ecological safety. Methods: Through systematic literature analysis, we identified key species, including Geukensia demissa, Daphnia magna, and Anadara granosa, which demonstrated measurable success in the remediation of aquatic environments contaminated with heavy metals and organic pollutants. Additionally, soil-dwelling nematodes such as Caenorhabditis elegans and Cephalobus persegnis play critical roles in hydrocarbon degradation and in enhancing microbial synergy in polluted substrates. These findings highlight the diverse functional capacities of animals in bioremediation efforts. The methodology employed in this study is a comprehensive literature review, focusing on peer-reviewed articles published over the last two decades. Results: This review synthesizes findings related to pollutant types, animal species used in zooremediation, remediation outcomes, and ecological impacts. By critically examining existing studies, the evaluation identifies trends, gaps, and challenges in the application of zooremediation. Conclusion: Future research should focus on understanding the long-term impacts, optimizing protocols, and safeguarding both ecological and animal health to fully realize the potential of zooremediation in managing environmental pollution on a global scale.